Outcomes of convergent atrial fibrillation ablation with continuous rhythm monitoring. (6th April 2020) - Larson, John; Merchant, Faisal M.; Patel, Akshar; Ndubisi, Nnaemeka M.; Patel, Anshul M.; DeLurgio, David B.; Lloyd, Michael S.; El‐Chami, Mikhael F.; Leon, Angel R.; Hoskins, Michael H.; Keeling, W. Brent; Halkos, Michael E.; et al.
Abstract: Background: Outcomes of catheter ablation for persistent atrial fibrillation (PeAF) are suboptimal. The convergent procedure (CP) may offer improved efficacy by combining endocardial and epicardial ablation. Methods: We reviewed 113 consecutive patients undergoing the CP at our institution. The cohort was divided into two groups based on the presence (n = 92) or absence (n = 21) of continuous rhythm monitoring (CM) following the CP. Outcomes were reported in two ways. First, using a conventional definition of any atrial fibrillation/atrial tachycardia (AF/AT) recurrence lasting >30 seconds, after a 90 day blanking period. Second, by determining AF/AT burden at relevant time points in the group with CM. Results: Across the entire cohort, 88% had either persistent or long‐standing persistent AF, mean duration of AF diagnosis before the CP was 5.1 ± 4.6 years, 45% had undergone at least one prior AF ablation, 31% had impaired left ventricle ejection fraction and 62% met criteria for moderate or severe left atrial enlargement. Mean duration of follow‐up after the CP was 501 ± 355 days. In the entire cohort, survival free from any AF/AT episode >30 seconds at 12 months after the blanking period was 53%. However, among those in the CM group who experienced recurrences, mean burden of AF/AT was generally very low (<5%) and remained stable over the duration of follow‐up. Ten patients (9%) required elective cardioversion outside the 90 day blanking period, 11 patients (9.7%) underwent repeat ablation at a mean of 229 ± 178 days post‐CP and 64% were off AADs at the last follow‐up. Procedural complications decreased significantly following the transition from transdiaphragmatic to sub‐xiphoid surgical access: 23% versus 3.8% ( P  = .005) Conclusions: In a large, consecutive series of patients with predominantly PeAF, the CP was capable of reducing AF burden to very low levels (generally <5%), which appeared durable over time. Complication rates associated with the CP decreased significantly with the transition from transdiaphragmatic to sub‐xiphoid surgical access. Future trials will be necessary to determine which patients are most likely to benefit from the convergent approach.